Em busca da organização do conhecimento: a gestão da informação nas bases de dados da Previdência Social brasileira com o uso da abordagem de análise de domínio - Ribeiro, Cláudio José Silva (2001)
In order to develop knowledge organization process within a given context, to understand the information environment, application systems and there data as well as its information stocks and information flow. The present work studies the use of Domain Analysis approach as an artifact to support the knowledge organization process at the Brazilian Social Security. In this context it is presented the essence of the relation between data and information on the basis of the concept of relevance and on the use of Domain Analysis. Taking into consideration the information questions in the Social Security and on its efforts towards knowledge organization in the last few years. The JAD technique was used as a tool to conduct the investigation. The results obtained may contribute to the generation of better products to make available a wider set of social security and social assistance information increasing the relationships between the State and Citizens